2021
DOI: 10.1038/s41598-021-03870-z
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis indices are related to diabetic peripheral neuropathy in individuals with type 2 diabetes

Abstract: The association between nonalcoholic fatty liver (NAFL) or liver fibrosis and diabetic peripheral neuropathy (DPN) has not been well studied. We aimed to investigate the association of NAFL or liver fibrosis indices and DPN in individuals with type 2 diabetes. In this observational study, we included 264 individuals with type 2 diabetes, and calculated non-alcoholic fatty liver disease (NAFLD) liver fat score, NAFLD fibrosis score, and Fibrosis-4 (FIB-4) index to evaluate the status of NAFLD or liver fibrosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
7
1
Order By: Relevance
“…We found the positive association between NAFLD and PN in our study and maybe it is needed to explore whether NAFLD is associated with other microvascular complications in future studies. Another study 20 recruited 264 individuals with type 2 diabetes from Seoul, Korea. The study suggested that the NAFLD fibrosis score (NFS) and Fibrosis-4 (FIB-4) index were associated with DPN among patients with a high NAFLD liver fat score (> − 0.640).…”
Section: Discussionmentioning
confidence: 99%
“…We found the positive association between NAFLD and PN in our study and maybe it is needed to explore whether NAFLD is associated with other microvascular complications in future studies. Another study 20 recruited 264 individuals with type 2 diabetes from Seoul, Korea. The study suggested that the NAFLD fibrosis score (NFS) and Fibrosis-4 (FIB-4) index were associated with DPN among patients with a high NAFLD liver fat score (> − 0.640).…”
Section: Discussionmentioning
confidence: 99%
“…In light of this data, our study supports the notion that the prevalence of severe fibrosis, the main determinant of mortality in NAFLD, is higher in patients with metabolic alterations. Other studies found a bidirectional correlation between liver fibrosis and peripheral diabetic neuropathy, suggesting possible common etiological mechanisms [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 95%
“…As mentioned earlier, AAR, an emerging indicator of liver function, has been reported to effectively predict the severity of liver fibrosis in patients with various liver disease including NAFLD (10,11). There is now growing evidence that NAFLD is more common and often advanced in patients with T2DM, easily progressing to nonalcoholic steatohepatitis and advanced liver fibrosis, than in the general population (6,(43)(44)(45)(46). Considering a certain intrinsic correlation among AAR, NAFLD and liver fibrosis, and diabetic vascular complication (6,10,11,(15)(16)(17)(18)(19)(43)(44)(45)(46), it is plausible that AAR may be associated with the presence of DPN, and high AAR may be an early signal for being at risk for DPN.…”
Section: Discussionmentioning
confidence: 99%
“…There is now growing evidence that NAFLD is more common and often advanced in patients with T2DM, easily progressing to nonalcoholic steatohepatitis and advanced liver fibrosis, than in the general population (6,(43)(44)(45)(46). Considering a certain intrinsic correlation among AAR, NAFLD and liver fibrosis, and diabetic vascular complication (6,10,11,(15)(16)(17)(18)(19)(43)(44)(45)(46), it is plausible that AAR may be associated with the presence of DPN, and high AAR may be an early signal for being at risk for DPN. In the present study, we found that patients with higher AAR quartiles tended to have higher VPT, a widely recommended indicator of the presence and severity of confirmed clinical neuropathy (47), and similarly, patients with DPN had significantly higher AAR than those without.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation